2003
DOI: 10.1038/sj.onc.1206786
|View full text |Cite
|
Sign up to set email alerts
|

HER2/neu reduces the apoptotic effects of N-(4-hydroxyphenyl)retinamide (4-HPR) in breast cancer cells by decreasing nitric oxide production

Abstract: The retinoid N-(4-hydroxyphenyl)retinamide (4-HPR also known as fenretinide) is a potent inducer of apoptosis in breast cancer cells. We observed a 4.5-fold reduction in 4-HPR-mediated apoptosis in MCF-7 breast cancer cells transfected with HER2/neu (MCF-7/HER2) as compared with the parental MCF-7 (MCF-7/WT) cells. Blocking HER2/neu with trastuzumab (Herceptin TM ) led to a sixfold increase in 4-HPR-induced apoptosis in HER2/neuoverexpressing cells. These data indicate that HER2/neu reduces the sensitivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 49 publications
(53 reference statements)
1
32
0
Order By: Relevance
“…We reported recently that HER2/neu increases the resistance of breast cancer cells to N-(4-hydroxyphenyl)retinamide (4-HPR) by suppressing the production of the apoptotic molecule nitric oxide (NO; Ref. 2). However, the identities of the downstream signaling proteins used by HER2/neu to induce these effects are not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported recently that HER2/neu increases the resistance of breast cancer cells to N-(4-hydroxyphenyl)retinamide (4-HPR) by suppressing the production of the apoptotic molecule nitric oxide (NO; Ref. 2). However, the identities of the downstream signaling proteins used by HER2/neu to induce these effects are not known.…”
Section: Introductionmentioning
confidence: 99%
“…COX-2 catalyzes the conversion of arachidonic acid to prostaglandins (PGs). High levels of COX-2 and its main product, PGE 2 , have been found in human breast cancer cells and tumors that overexpress HER2/neu but not in normal breast tissue (4,5). COX-2 overexpression increases resistance to apoptosis, particularly NO-mediated apoptosis (4,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that 4-HPR induce cancer cell apoptosis by increasing ROS generation (Kim et al, 2006). The production of nitric oxide induced by nitric oxide synthase has also been proposed as a mechanism by which 4-HPR suppresses cancer cell growth and induces apoptosis (Simeone et al, 2002(Simeone et al, , 2003. 4-HPR can act as a potent inhibitor of mammary carcinogenesis (Moon and Mehta, 1989) to suppress tumor growth and inhibit telomerase activity in animal models (Bednarek et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms underlying the apoptotic effect of fenretinide are not yet well defined, but it has recently become evident that 4-HPR-mediated apoptosis is tissue specific and that multiple mechanisms may operate within specific tissues . Both elevations in the levels of the sphingolipid ceramide (Maurer et al 2000) and the production of nitric oxide (NO) by nitric oxide synthases (NOS) (Simeone et al 2002(Simeone et al , 2003 have been implicated in fenretinide-mediated apoptosis in breast cancer cells. A mechanism specific to fenretinide as compared with other retinoids is the generation of reactive oxygen species (ROS), such as hydrogen peroxide and superoxide, which seem to be critical in mediating apoptosis in different cancer cell types (Delia et al 1997, Oridate et al 1997, Tosetti et al 2003.…”
Section: The Synthetic Retinoid Fenretinidementioning
confidence: 99%
“…One of the mechanisms involved is a decrease in NO production mediated by NOS, resulting from induction of cyclooxygenase-2 (COX-2) expression by HER-2/neu through activation of Akt (Simeone et al 2003. Interestingly, however, fenretinide has been found to down-regulate c-erbB-2 protein and mRNA in overexpressing breast cancer cell lines and to induce apoptosis also in HER-2/neu-transformed cells (Rao et al 1998, Jinno et al 1999, a phenotype which is known to be tamoxifen resistant.…”
Section: The Synthetic Retinoid Fenretinidementioning
confidence: 99%